2015
DOI: 10.1159/000438597
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Myocardial Hypoxia-Reoxygenation Injury by Inhibiting Autophagy via mTOR Activation

Abstract: Background: Autophagy plays a significant role in myocardial ischemia reperfusion (IR) injury. Hydrogen sulfide (H2S) has been demonstrated to protect cardiomyocytes against IR injury, while whether it has anti-autophagy effect has not been known. The aim of this study was to investigate whether H2S regulates autophagy during IR injury and its possible mechanism. Methods and Results: The cardiomyocytes of neonatal rats were randomized into Con, hypoxia-reoxygenation (HR) and H2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…PI3K/AKT signal pathway is an important pathway for protecting myocardial cells against hypoxia-induced injury [35, 36]. Xiao et al reported that hydrogen sulfide protects myocardial cells against hypoxia-induced injury via mTOR activation [37]. Chen et al reported that lipoxin A4-induced heme oxygenase-1 protects cardiomyocytes against hypoxia/reoxygenation injury via p38 MAPK activation and Nrf2/ARE complex [38].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT signal pathway is an important pathway for protecting myocardial cells against hypoxia-induced injury [35, 36]. Xiao et al reported that hydrogen sulfide protects myocardial cells against hypoxia-induced injury via mTOR activation [37]. Chen et al reported that lipoxin A4-induced heme oxygenase-1 protects cardiomyocytes against hypoxia/reoxygenation injury via p38 MAPK activation and Nrf2/ARE complex [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H 2 S was reported to have a neuroprotective effect against the cognitive diseases [38-40]. The proposed mechanisms underlying the protective effect of H 2 S involved oxidative stress [25] and autophagy [41]. …”
Section: Discussionmentioning
confidence: 99%
“…As a sensor of the cellular nutrient status, mTOR is inhibited during energy insufficiency and has been identified as a negative regulator of autophagy in mammalian cells [16, 19, 20]. AMP-activated protein kinase (AMPK) is a protein kinase member that can be activated by a reduction in the intracellular ATP/AMP ratio [21].…”
Section: Resultsmentioning
confidence: 99%